(untitled) (Journal of Geography and Environmental Management, 2017)
The article describes the technique and presents the results of research into the properties of prototypes of electrically heated double-glazed windows. The types of energy-saving layers of double-glazed windows are considered: K-coating and I-coating. Comparison of thermal characteristics of windows with energy-saving glasses and with ordinary double-glazed windows was performed, which showed that a single-compartment glass unit with energy-saving glass is more effective than a double-glazed unit. In this case, double glazing with I - glasses are more energy efficient than with K - glasses. The mechanical properties and heat resistance of tempered glass are studied, which depend on the degree of quenching. The process of injecting inert gases, argon or krypton into the chambers between the glasses, is considered to reduce heat loss from convective heat transfer. This procedure improves the characteristics of light-transmitting structures with an energy-saving coating. Thermal fields in the glass plane are also analyzed. The possibility of measuring the characteristics of thermoelastic states arising during the heating of a glass unit is demonstrated. When conducting studies of electrical and thermophysical characteristics of insulating glass units, leakage currents, the power of insulating glass units at operating temperature and the resistance of conductive paths were measured. This article discusses the advantages of using energy-saving glasses, as well as the scheme of action of energy-saving glass in summer and winter. Energy-saving glass is a new turn in a variety of programs to reduce heat losses and can be used for energy saving in residential and industrial buildings.